Comparison Of Financial Performance Based On The Implementation Of PSAK 30 And PSAK 73 On Leases In Energy Industry Companies - Lisca Putri; Nurna Aziza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
A finance operation that takes the form of supplying capital goods is called leasing. PSAK 30 will be replaced with PSAK 73, which was accepted from IFRS 16, on January 1, 2020. The purpose of this study is to compare the financial performance of the organization using leases for PSAK 30 and PSAK 73. A quantitative descriptive strategy is employed in this investigation. 67 firm samples were obtained using the purposive sampling approach from the population of 74 enterprises that made up the research. The firms in the energy industry sector that are listed on the Indonesia Stock Exchange during the 2019–2020 research period are the focus of this study. Ratio analysis, descriptive statistical analysis, regression analysis (which includes the normality test and the Wilcoxon signed rank test), and hypothesis testing are the data analysis techniques used in this work. According to the study's findings, which were derived from the use of descriptive statistics, hypothesis testing, and ratio analysis test, there is a difference in the financial performance of transportation firms listed on the Indonesia Stock Exchange when PSAK 30 and PSAK 73 are implemented.